Innate Signaling in the CNS Prevents Demyelination in a Focal EAE Model - Dubik, Magdalena; Marczynska, Joanna; Mørch, Marlene T.; Webster, Gill; Jensen, Kirstine Nolling; Wlodarczyk, Agnieszka; Khorooshi, Reza; Owens, Trevor (Frontiers in Neuroscience, 2021)
The pathological hallmark of multiple sclerosis (MS) is the formation of multifocal demyelinating lesions in the central nervous system (CNS). Stimulation of innate receptors has been shown to suppress experimental autoimmune encephalomyelitis (EAE), an MS-like disease in mice. Specifically, targeting Toll-like receptor 9 (TLR9) and NOD-like receptor 2 (NOD2) significantly reduced disease severity. In the present work we have developed a novel focal EAE model to further study the effect of innate signaling on demyelinating pathology. Focal lesions were induced by stereotactic needle insertion into the corpus callosum (CC) of mice previously immunized for EAE. This resulted in focal pathology characterized by infiltration and demyelination in the CC. We find that intrathecal delivery of MIS416, a TLR9 and NOD2 bispecific innate ligand, into the cerebrospinal fluid reduced focal lesions in the CC. This was associated with upregulation of type I and II interferons, interleukin-10, arginase-1, CCL-2 and CXCL-10. Analysis of draining cervical lymph nodes showed upregulation of type II interferons and interleukin 10. Moreover, intrathecal MIS416 altered the composition of early CNS infiltrates, increasing proportions of myeloid and NK cells and reducing T cells at the lesion site. This study contributes to an increased understanding of how innate immune responses can play a protective role, which in turn may lead to additional therapeutic strategies for the prevention and treatment of demyelinating pathologies.